FORMATION OF 3-VERTEX METALLABORANES FROM MONOBORANE PRECURSORS - X-RAY CRYSTAL-STRUCTURES OF THE MOLYBDENUM AND RUTHENIUM COMPLEXES [MO(ETA-C5H5)2H(ETA-2-B2H5)] AND [RU(ETA-C5ME5)(PME3)(ETA-2-B2H7)] - Grebenik, P; Green, M; Kelland, M; Leach, J; Mountford, P; Stringer, G; Walker, N; Wong, L (1988)
The novel three-vertex metallaborane [Ru(η-C5Me 5)(PMe3)(η2-B2H7)] (1) has been synthesised by reaction of [Ru(η-C5Me 5)(PMe3)Cl2] with NaBH4; homologation is also observed in the reaction of [Mo(η-C5H 5)2H2] with BH3·THF, which forms [Mo(η-C5H5)2H(η2- B2H5)] (2); X-ray crystal structures of compounds (1) and (2) are reported.